Assessing the impact of biochar and nitrogen application on yield, water-nitrogen use efficiency and quality of intercropped maize and soybean - Wang, Lixue; Yu, Binhang; Ji, Jianmei; Khan, Ismail; Li, Guanlin; Rehman, Abdul; Liu, Dan; Li, Sheng (Frontiers in Plant Science, 2023)
Introduction Biochar (BC) and nitrogen (N) application have the potential to increase grain yield and resource use efficiency in intercropping systems. However, the effects of different levels of BC and N application in these systems remain unclear. To address this gap, the study is intended to ascertain the impact of various combinations of BC and N fertilizer on the performance of maize-soybean intercropping and determine the optimum application of BC and N for maximizing the effect of the intercropping system. Methods A two-year (2021-2022) field experiment was conducted in Northeast China to assess the impact of BC (0, 15, and 30 t ha-1) and N application (135, 180, and 225 kg ha-1) on plant growth, yield, water use efficiency (WUE), N recovery efficiency (NRE) and quality in an intercropping system. Maize and soybean were selected as materials in the experiment, where every 2 rows of maize were intercropped with 2 rows of soybean. Results and discussion The results showed that the combination of BC and N significantly affected the yield, WUE, NRE and quality of intercropped maize and soybean. The treatment of 15 t ha-1 BC and 180 kg ha-1 N increased grain yield and WUE, while that of 15 t ha-1 BC and 135 kg ha-1 N enhanced NRE in both years. Nitrogen promoted the protein and oil content of intercropped maize, but decreased the protein and oil content of intercropped soybean. BC did not enhance the protein and oil content of intercropped maize, especially in the first year, but increased maize starch content. BC was found to have no positive impact on soybean protein, but it unexpectedly increased soybean oil content. The TOPSIS method revealed that the comprehensive assessment value first increased and then declined with increasing BC and N application. BC improved the performance of maize-soybean intercropping system in terms of yield, WUE, NRE, and quality while N fertilizer input was reduced. The highest grain yield in two years was achieved for BC of 17.1-23.0 t ha-1 and N of 156-213 kg ha-1 in 2021, and 12.0-18.8 t ha-1 BC and 161-202 kg ha-1 N in 2022. These findings provide a comprehensive understanding of the growth of maize-soybean intercropping system and its potential to enhance the production in northeast China.